Critical Study of Sociocultural Practice in Cattle Trading Arena - Sujarwa Sujarwa; Andrik Purwasito; Sri Kusuma Habsari; Titis Srimuda Pitana (CHANNEL: Jurnal Komunikasi, 2021)
In the cattle trading arena, it is suspected that there is a peculiarity of registers as a style and rhetorical discourse of disguised communication as a form of tactics, which is not in line between linguistic aspects and sociocultural behavior. Register as a rhetorical style of communication is built, of course not without reason, but there is motivation, intention, and achievement of communication goals. This paper attempts to reveal: the form of registers in the rhetoric of communication in the cattle trading arena, the function of the register as communication rhetoric in the cattle trading arena, the symbolic meaning of registers in the rhetorical style and discourse of sociocultural practice in the cattle trading arena. A qualitative descriptive method is used to describe substantially the aspects of the meaning of the data with an in-depth analysis related to the subject matter. In order to achieve a profound interpretation, theoretical aids are needed: sociocultural, sociolinguistic, stylistic, capitalism, hegemony, discourse theory. In addition, hermeneutic theory as a strategic method for understanding texts must be interpreted for meaning. The results showed: the form of registers in the rhetoric of communication in the cattle trading arena in the form of oratorical, deliberative, consultative, casual, and intimate. The study concludes that the register functions as a conative and emotive tactic to influence, weaken, subdue, and restrain hegemony from creating an atmosphere of domination. The register applied in the rhetoric of communication in the cattle trading arena contains the symbolic meaning of feudalism relations in the form of phenomena of sociocultural practice events influenced by the discourse of tactics for capitalist cultural domination.